A novel look at Thailand's tourism from a tourism composite index. (13th November 2021) - Soh, Ann-Ni; Chong, Mei-Teing; Puah, Chin-Hong
The number of international tourists has reached more than half of Thailand's population, and tourism receipts accounted for nearly one-fifth of its GDP, which shows that the tourism industry is greatly affecting Thailand's economic growth. Therefore, changes in the tourism industry are part of the lifeline of Thailand's economy and deserve attention. The principal objective is to construct a tourism composite index (TCI) for Thailand by employing the indicator construction method, filtering extraction, turning points detection and directional accuracy test in predicting significant changes of the tourism economy. Findings unveil that the major transitions in the Thailand tourism cycle can be predicted by the constructed TCI with an average lead time of 2.75 months and an accuracy rate up to 64%. A series of risk management, tourism planning, marketing strategies can be informed by using this index. It is indeed beneficial for tourism industry practitioners and decision-makers for their strategic decision-making.